ANALISIS PENDAPATAN USAHA GULA MERAH KELAPA (Studi Kasus Di Desa Medono Kecamatan Kaliwiro Kabupaten Wonosobo) - Mugiono Mugiono; Sri Marwanti; Shofia Nur Awami (Universitas Wahid Hasyim, 2014)
Sugar is one of the staple food of Indonesia's population. Coconut sugar agro-industry currently has a pretty good prospect and to increase household income. One of the coconut sugar producing areas located in the Medono Village, Kaliwiro District, Wonosobo Regency. This study aims to determine the total cost of one month of production and revenue from the business of making coconut sugar, knowing one month production revenues from the business of making coconut sugar and determine the feasibility of the business of making coconut sugar in Medono Village Kaliwiro District Wonosobo Regency. Research using descriptive analytical methods and sampling in this study with sampling purpose, it obtained receipts of Rp 803,763.50 and income of Rp 456,097.96 per month. Based on the analysis of the feasibility of the R/C obtained value of R/C of 2,3 means that the business is economically feasible to be developed. Value for one month production, unit BEP has a number of 57 kilograms and revenue BEP of Rp. 39,212.00. Keywords: Coconut sugar, farmers, revenue